An interview with Avigail Eisenberg: “Reasoning about the Identity of Aboriginal People” - Blanchard, Martin (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2006)
Avigail Eisenberg is an Associate Professor in the Department of Political Science, University of Victoria. She was also a fellow of CRÉUM during the 2004-2005 academic year. She has written important work on the issues of identity, race, gender, minority rights, and in particular, Aboriginal claims. Her writing displays intelligent and acute commentaries in which she demonstrates an ability to tackle difficult questions in a refreshing way.A list of her publications is available at http://web.uvic.ca/polisci/eisenberg/pubs.htm.Martin Blanchard of CRÉUM asked Professor Eisenberg if she would be willing to be interviewed via email on the subject of an article she had just finished writing, entitled “Reasoning about the Identity of Aboriginal People”. (This text is forthcoming in Accommodating Cultural Diversity: Contemporary Issues in Theory and Practice, Stephen Tierney ed., London: Ashgate.) She kindly accepted to answer his questions.